Genome-wide characterization of the Csa-miR156 family revels its dynamic role in drought stress response in cucumber - Lili Guan; Lei Zhou; Qian Yu; Yanchang Jiang; Defang Gan (Horticulture, Environment, and Biotechnology, 2026)

Characteristics of the MAPK gene family in Zizania latifolia and MAPK3 role in response to fungal pathogen infection - Lijun Xu; Pengfei Guo; Yong Kuang; Ke Su; Keling Hu; Defang Gan (Journal of Genetics, 2025)

Genome-wide analysis of BrbHLH gene family and functional identification of the involvement of BcbHLH57 in abiotic stress in wucai (Brassica campestris L.) - Bingsheng Zhang; Liting Zhang; Tian Lan; Shidong Zhu; Jinfeng Hou; Guohu Chen; Xiaoyan Tang; Defang Gan; Chenggang Wang; Lingyun Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)
Wucai ( Brassica campestris L. ssp. chinensis var. rosularis Tsen) is a subspecies of Brassica campe stris , is a kind of cold-tolerant vegetable widely cultivated in the Yangtze-Huai River Basin of China. To breed new varieties of resistance to stress, it is necessary to study the tolerance of Resistance to different stresses. Transcriptomic data showed that exogenous application of 2, 4-epbrassinolide (EBR) significantly increased the bHLH genes expression in wucai at low temperature, and bHLH57 was up regulated significantly. BHLH (Basic helix-loop-helix) TFs (transcription factor) is a superfamily of TFs with complex functions and related to various plant life activities. In this study, a total of 239 bHLH genes were identified, and their amino acid physicochemical properties, chromosome location, gene structure, phylogeny and cis-acting elements were analyzed by bioinformatics. Phylogenetic analysis showed that bHLH gene families in Brassica rapa and Arabidopsis were divided into six groups, and the distribution of bHLH genes in Brassica rapa was uneven. The BrbHLH s were irregularly mapped in the cultivated B. rapa genome. The maximum number (40) of BrbHLH genes were mapped on Chr09. In addition, there were tandem repeats in some genes. The collinearity analysis showed that 152 AtbHLH genes and 239 BrbHLH protein genes formed 296 collinearity pairs, and the Ka/Ks ratio ofall duplicated BrbHLH gene pairs had a Ka/Ks ratio of < < 1, indicating that the bHLH family genes may have undergone strong purification and selection during the evolution process. Cis-acting elements analysis showed that the promoter region of bHLH family genes in Brassica rapa had more responsive elements related to light, hormone and abiotic stress. The BcbHLH57 overexpressing Arabidopsis thaliana lines were subjected to different stress treatments, and the seed germination rate, root growth, survival rate and various plant physiological indexes were determined. The results showed that the transgenic lines were more tolerant to salt, heat and drought stress. In this study, the response of BcbHLH57 gene to salt, heat and drought stress was reported for the first time, which provided a basis for further research on the function of BcbHLH57 in abiotic stress.

Expression analysis of argonaute, Dicer-like, and RNA-dependent RNA polymerase genes in cucumber (Cucumis sativus L.) in response to abiotic stress - DEFANG GAN; MENGDAN ZHAN; FENG YANG; QIQI ZHANG; KELING HU; WENJUAN XU; QINGHUI LU; LING ZHANG; DANDI LIANG (Journal of Genetics, 2017)

Genome-Wide Identification of the Dicer-Like, Argonaute, and RNA-Dependent RNA Polymerase Gene Families in Cucumber (Cucumis sativus L.) - Defang Gan; Dandi Liang; Jiao Wu; Mengdan Zhan; Feng Yang; Wenjuan Xu; Shidong Zhu; Jiayin Shi (Journal of Plant Growth Regulation, 2016)

Genome-wide analysis of HD-Zip genes in grape (Vitis vinifera) - Haiyang Jiang; Jing Jin; Huan Liu; Qing Dong; Hanwei Yan; Defang Gan; Wei Zhang; Suwen Zhu (Tree Genetics & Genomes, 2015)

Identification and characterization of the RCI2 gene family in maize (Zea mays) - YANG ZHAO; HAIQING TONG; RONGHAO CAI; XIAOJIAN PENG; XIAOYU LI; DEFANG GAN; SUWEN ZHU (Journal of Genetics, 2014)

Application of RNA interference methodology to investigate and develop SCMV resistance in maize - DEFANG GAN; FEI DING; DAN ZHUANG; HAIYANG JIANG; TONG JIANG; SUWEN ZHU; BEIJIU CHENG (Journal of Genetics, 2014)

Identification and expression analysis of primary auxin-responsive Aux/IAA gene family in cucumber (Cucumis sativus) - DEFANG GAN; DAN ZHUANG; FEI DING; ZHENZHOU YU; YANG ZHAO (Journal of Genetics, 2013)

Genome-wide analysis of BURP domain-containing genes in Maize and Sorghum - Defang Gan; Haiyang Jiang; Jiao Zhang; Yang Zhao; Suwen Zhu; Beijiu Cheng (Molecular Biology Reports, 2011)

Bacterially expressed dsRNA protects maize against SCMV infection - Defang Gan; Jiao Zhang; Haibo Jiang; Tong Jiang; Suwen Zhu; Beijiu Cheng (Plant Cell Reports, 2010)